Influencia del estres hidrico y de la temperatura sobre el crecimiento de Euphorbia lathyris - Ventas, P.=700 1 Tenorio, J.L.; Funes, E.; Rodriguez-Maribona, B.; Ayerbe, L.
(Es, En)
ilus., 23 ref.
Keywords: EUPHORBIA LATHYRIS; ESTRES; CRECIMIENTO; COMBUSTIBLES; ESPAÑA; ESTRES HIDRICO